Impact of weight loss and eating difficulties on health-related quality of life up to 10 years after oesophagectomy for cancer. Issue 4 (21st November 2017) - Anandavadivelan, P.; Wikman, A.; Johar, A.; Lagergren, P.
Abstract: Background: Severe weight loss is experienced by patients with eating difficulties after surgery for oesophageal cancer. The aim of this prospective cohort study was to asssess the influence of eating difficulties and severe weight loss on health-related quality of life (HRQoL) up to 10 years after oesophagectomy. Methods: Data on bodyweight and HRQoL were collected at 6 months, 3, 5 and 10 years in patients who underwent surgery for oesophageal cancer in Sweden between 2001 and 2005. Exposures were percentage weight loss, and eating difficulties defined by the European Organisation for Research and Treatment of Cancer ( EORTC) QLQ-OES18 questionnaire. Outcomes were HRQoL scores from the EORTC QLQ-C30 questionnaire. Repeated-measures ANOVA, adjusting for potential confounders, was used to assess the association between eating difficulties and weight loss (4 exposure groups) and HRQoL scores at each time point. Mean score differences (MDs) between time points or exposure groups were defined as clinically relevant in accordance with evidence-based interpretation guidelines. Results: In total, 92 of 104 10-year survivors (88·5 per cent) responded to the questionnaires. Weight loss was greatest within 6 months of surgery. Patients with eating difficulties with or without weight loss reported clinically and statistically significantly worsened HRQoL in almost all aspects. The largest MD was seen between 5 and 10 years after surgery for global quality of life, physical, role and social function (MD –22 to –30), as well for fatigue, nausea, dyspnoea, insomnia, appetite loss and diarrhoea (MD 24–36). Conclusion: Eating difficulties are associated with deterioration in several aspects of HRQoL up to 10 years after surgery for oesophageal cancer.